Sustainable Lifestyle Education: An Ecobrick Module for Enhancing Students’ Creativity in Pancasila Student Profile Projects - Gagaramusu, Yusdin; Azizah; Arianto; Kaharu, Sarintan N; Zulnuraini; Rahayu, Adelya Putri; Aditya, Asania Dwi; Sitepu, Melyani Sari (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the lack of project modules to strengthen the Pancasila student profile (P5) that promote the use of plastic waste in learning. This study aims to develop an ecobrick module as a project to strengthen the Pancasila student profile (P5) by utilizing plastic waste to improve students' creative dimensions. The project module developed is named the ecobrick module. This study uses a research and development method with the ADDIE development model. Data were collected using questionnaires and creative dimension observation sheets, then analyzed descriptively using qualitative and quantitative methods. The study involved 26 students, selected through a saturated sampling technique. The feasibility test scored 78.3 (good) from media experts and 94.66 (very good) from material experts, confirming the module's high feasibility. The practicality test showed very good responses from students (86.725) and teachers (95.53), confirming the module's high practicality. Furthermore, the effectiveness test of the module on the creative dimension of students was analyzed using the t-test. The results of the analysis showed a significance value of 0.000 <0.05, thus accepting the Ha hypothesis and rejecting the H0 hypothesis. This means that the P5 module (ecobrick module) is effective in improving students' creative dimensions. It can be concluded that the innovation of the P5 module (ecobrick) on sustainable lifestyle is valid, practical, and effective in enhancing students' creativity. In addition to improving students' creativity, this study has implications for the growth of environmental awareness through the utilization of plastic waste that can be continued.